Errors and productivity on the English past tense among Filipino L2 English learners - Reig, Christine Angeline; Flores, Dianne A; Molinar, Trizia Charlysle M; Castro, Maria Corazon Saturnina (Universitas Sarjanawiyata Tamansiswa, 2024)
The ubiquity of online communication in the 21st century provides a new medium for scholars to observe various linguistic phenomena, including studies on English as a second and foreign language. In this study, morphological errors and productivity among Filipino L2 English learners, who are also active users of Facebook, were explored—particularly with their formation of the past tense of English verbs. To conduct the study, the researchers drew methods from Ellis and Barkhuizen’s (2009) Error Analysis framework and Aronoff and Schvaneveldt’s (1978) framework for testing morphological productivity. Using these frameworks, the main findings show that the -ed suffix remains a salient structure for forming the English past tense. Aside from being the most productive structure, the findings show that most errors in the participants’ formation of the past tense of English verbs involve using the -ed suffix in place of the appropriate structures (such as the zero and replacive structures). This finding may be explained by L2 learners’ overgeneralization of the rule to use the -ed suffix in forming the past tense of regular English verbs. In line with these findings, language teachers and policymakers may develop procedures for intervention and reinforcement to address the overgeneralization of rules to structures where they do not apply. At the same time, the findings provide insights into the implications of the rise of online communication in language learning, including the challenges and opportunities it presents in addressing linguistic deviations.